2021
DOI: 10.1371/journal.pone.0253202
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and recognition of breast ultrasound images based on an expanded U-Net

Abstract: This paper establishes a fully automatic real-time image segmentation and recognition system for breast ultrasound intervention robots. It adopts the basic architecture of a U-shaped convolutional network (U-Net), analyses the actual application scenarios of semantic segmentation of breast ultrasound images, and adds dropout layers to the U-Net architecture to reduce the redundancy in texture details and prevent overfitting. The main innovation of this paper is proposing an expanded training approach to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…25 Guo et al have suggested an expanded UNet that included seven dropout layers in the original UNet to segment tumors from ultrasound images. 26 The Intersection over Union (IoU) coefficient of the expanded UNet was 11.0 units larger than the IoU coefficient of the original UNet.…”
Section: Deep Learning-based Methods For the Detection Of Mri Breast ...mentioning
confidence: 99%
“…25 Guo et al have suggested an expanded UNet that included seven dropout layers in the original UNet to segment tumors from ultrasound images. 26 The Intersection over Union (IoU) coefficient of the expanded UNet was 11.0 units larger than the IoU coefficient of the original UNet.…”
Section: Deep Learning-based Methods For the Detection Of Mri Breast ...mentioning
confidence: 99%
“…In order to find the pixels in the image that have the greatest impact on the deep learning results, the logical relationship between the input and the output is judged by studying the influence of the input layer changes on the output results. Using backpropagation [ 19 ] and combining gradients, network weights, or activations [ 42 , 43 ] track information, and the network output tracks its input or intermediate hidden layers. Reference [ 43 ] filtered gradients through an optimization process to further extract fine-grained regions for specific prediction evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Using backpropagation [ 19 ] and combining gradients, network weights, or activations [ 42 , 43 ] track information, and the network output tracks its input or intermediate hidden layers. Reference [ 43 ] filtered gradients through an optimization process to further extract fine-grained regions for specific prediction evidence. The core of these methods is to find the most representative perturbations through detailed search or optimization.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the computer treats this color image as three 512x512 matrices for three different color channels. This is performed on 2D matrices by image processing methods such as convolution and pooling [14,15]. Blur, sharpen, edge detection, noise reduction, etc.…”
Section: Convolutionmentioning
confidence: 99%